A comprehensive review on solar to thermal energy conversion and storage using phase change materials - Tripathi B.M.; Shukla S.K.; Rathore P.K.S. (My University, 2025)
Renewable energy plays a pivotal role for mankind in the times of adverse climate change and global warming. However, renewable energy such as solar energy comes with inherent drawbacks of limited or varying availability in terms of time, space and power. Consequently, it will lead to poor performance of numerous solar thermal technologies. To overcome these constraints of solar energy, Thermal Energy Storage (TES) can play a pivotal role in improving performance and feasibility of solar thermal technologies. TES using Phase Change Material (PCM) is one of the effective techniques of charging, storing, and discharging thermal energy as and when required. PCM stores thermal energy in the form of latent heat by undergoing phase change at constant temperature. However, PCM suffers with drawbacks of low thermal conductivity, poor solar to thermal conversion efficiency, and risk of leakage during phase transition. These thermo-physical properties limit the applicability of PCM as a potential TES material. In view of the above facts and findings, this study comprehensively analyses the above mentioned thermo-physical bottlenecks of PCMs. It briefly discusses TES, various materials for TES, PCM, and properties of PCM. In detail, it presents various methods and mechanisms of improving solar to thermal performance and thermal conductivity of the PCM. Additionally, this study presents a robust discussion on techniques of minimizing the leakage of the PCM during phase transformation. © 2023 Elsevier Ltd